1996
DOI: 10.1016/0925-4439(95)00107-7
|View full text |Cite
|
Sign up to set email alerts
|

Ageing is associated in females with a decline in the content and activity of the b-c1 complex in skeletal muscle mitochondria

Abstract: The activity of cytochrome-c oxidase [E.C. 1.9.3.1] and b-c(1) complex [E.C. 1.10.2.2.] and the content of cytochromes 6, c + c(1) and a + a(3) in human skeletal muscle mitochondria from orthopaedic patients (108 women and 68 males), of age ranging between 10 and 90 years, have been analyzed. The activity of cytochrome c-oxidase declines with age both in females and males, The activity of b-c(1) complex, which in young females is significantly higher than in young malts, declines sharply in females, but not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…27 Some sex-dependent differences in age-linked decline of mitochondrial respiration (eg specific activities of COX, NADH-cytochrome c reductase, UQH 2 -cytochrome c reductase) were also reported in humans. 28,29 There was reported lower COX activity in skeletal muscle in women than in men, but no differences in the CS activity were found. 30 In our study, no significant differences in the activities of COX and CS in lymphocytes were found between men and women, which is consistent with results of Pastoris et al, 31 who found no significant differences between males and females in the activities of various marker enzymes related to glycolysis, Krebs cycle and respiratory chain of human skeletal muscles.…”
Section: Effect Of Gendermentioning
confidence: 96%
“…27 Some sex-dependent differences in age-linked decline of mitochondrial respiration (eg specific activities of COX, NADH-cytochrome c reductase, UQH 2 -cytochrome c reductase) were also reported in humans. 28,29 There was reported lower COX activity in skeletal muscle in women than in men, but no differences in the CS activity were found. 30 In our study, no significant differences in the activities of COX and CS in lymphocytes were found between men and women, which is consistent with results of Pastoris et al, 31 who found no significant differences between males and females in the activities of various marker enzymes related to glycolysis, Krebs cycle and respiratory chain of human skeletal muscles.…”
Section: Effect Of Gendermentioning
confidence: 96%
“…23 decreased activity of individual electron chain complexes, 24,25 mitochondria DNA 26 and mitochondrial transcription. 26 The decay in mitochondrial function is attributed to oxygen stress and free radical production 27 .…”
Section: Agingmentioning
confidence: 97%
“…The decreased activity of citrate synthase in the mitochondria indicated that the age-related decline in skeletal muscle oxidative capacity is, most likely, the result of a decline in both mitochondrial content and function. Many other studies have shown an age-related decline in muscle mitochondrial content (8,30) and function (6,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%